2020
DOI: 10.3991/ijim.v14i01.11232
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Differences in the Study Plan of University Students

Abstract: <p class="0abstract">Effective study plan is a predictor of good academic performance. However, there are few evidences available on the role of gender and age in the study plan for students. This paper investigated the role of gender and age in the adoption of study plan that can guarantee success. A questionnaire was designed and administered to undergraduate students of a world class privately funded university located in Ogun State, Nigeria. Simple random sampling was used and 294 students responded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Incidentally, gender is considered as major intervening variable in most educational studies. Several studies reviewed by Okagbue et al (2020) gender differences and that of age are frequently investigated studies on cognitive abilities. In fact, Ramírez-Correa et al (2015) mentioned that the extant literature has often presented gender as a moderating variable of the Technology Acceptance Model, particularly within the context of e-learning.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Incidentally, gender is considered as major intervening variable in most educational studies. Several studies reviewed by Okagbue et al (2020) gender differences and that of age are frequently investigated studies on cognitive abilities. In fact, Ramírez-Correa et al (2015) mentioned that the extant literature has often presented gender as a moderating variable of the Technology Acceptance Model, particularly within the context of e-learning.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Likewise, the cognitive aspects in the field of education were frequently studied. For instance, many researchers [7] have found that the lack of significant gender differences means that the effect of the phenomenon under study is the same for both, men and women. If the study frequency is the same, regardless of the student's age and gender, it means that the students demonstrate the same patterns of behaviour regarding the study frequency.…”
Section: Introduction and Social Aspects Of The Topicality Of The Researchmentioning
confidence: 99%